Outcomes of Pancreatic Islet Allotransplantation Using the Edmonton Protocol at the University of Chicago. Issue 10 (October 2016) - Tekin, Zehra; Garfinkel, Marc R.; Chon, W. James; Schenck, Lindsay; Golab, Karolina; Savari, Omid; Thistlethwaite, J. Richard; Philipson, Louis H.; Majewski, Colleen; Pannain, Silvana; Ramachandran, Sabarinathan; Rezania, Kourosh; et al.
Abstract : Objective: The aim of this study was to assess short-term and long-term results of the pancreatic islet transplantation using the Edmonton protocol at the University of Chicago. Materials and Methods: Nine patients underwent pancreatic islet cell transplantation using the Edmonton Protocol; they were followed up for 10 years after initial islet transplant with up to 3 separate islet infusions. They were given induction treatment using an IL-2R antibody and their maintenance immunosuppression regimen consisted of sirolimus and tacrolimus. Results: Nine patients received a total of 18 islet infusions. Five patients dropped out in the early phase of the study. Greater than 50% drop-out and noncompliance rate resulted from both poor islet function and recurrent side effects of immunosuppression. The remaining 4 (44%) patients stayed insulin free with intervals for at least over 5 years (cumulative time) after the first transplant. Each of them received 3 infusions, on average 445 000 islet equivalent per transplant. Immunosuppression regimen required multiple adjustments in all patients due to recurrent side effects. In the long-term follow up, kidney function remained stable, and diabetic retinopathy and polyneuropathy did not progress in any of the patients. Patients' panel reactive antibodies remained zero and anti-glutamic acid decarboxylase 65 antibody did not rise after the transplant. Results of metabolic tests including hemoglobin A1c, arginine stimulation, and mixed meal tolerance test were correlated with clinical islet function. Conclusions: Pancreatic islet transplantation initiated according to Edmonton protocol offered durable long-term insulin-free glycemic control in only highly selected brittle diabetics providing stable control of diabetic neuropathy and retinopathy and without increased sensitization or impaired renal function. Immunosuppression adjustments and close follow-up were critical for patient retention and ultimate success.